The role of laboratory kidney parameters in predicting the outcomes of critical conditions in children in the early stages of care (Herald of the National Children's Medical Center, 2024)
Abstract: This article is devoted to determining the role of laboratory kidney parameters in the integral assessment of the condition and predicting the outcomes of children with critical conditions at the prehospital stage of emergency medical care.Materials and methods of research: The data from the medical history of 895 children were retrospectively studied and 143 children aged 12 to 18 years’ old who were in the NICU of the TashPMI clinic with somatic pathology and the presence of insufficiency of vital organ function were selected from them, who were admitted through the ambulance line of the city of Tashkent.Results of the study: A comparative analysis was carried out on the statistical parameters of the variables of the MMODS scale developed for the purpose of using at the stage of prehospital care based on a statistical analysis of the variable scales used in stationary conditions to determine diagnostic effectiveness. It was found that indicators of the level of urea, hourly diuresis and the presence of shaped elements (leukocytes and erythrocytes) in urine did not give positive results in statistical analysis, and they are less informative in terms of assessing severity and predicting outcomes, and indicators of serum creatinine and blood sodium levels are less informative in terms of assessing severity and predicting outcomes, and they can be used to assess the severity of the condition and predict outcomes in children.Conclusion: Urea levels, hourly diuresis, and the presence of shaped elements in urine are less informative in terms of assessing severity and predicting outcomes. Serum creatinine and blood sodium levels are less informative in terms of assessing severity and predicting outcomes, and they can be used to assess the severity of the condition and predict outcomes in children.
Keywords: critical conditions; scale; urea; hourly diuresis; leukocyte; erythrocyte; condition assessment; integral assessment; variables of integral scales; outcome; prognosis